Manajemen Kepemimpinan Kepala Sekolah - Fauzi, Ahmad (JIEM (Journal of Islamic Education Management), 2021)
Leadership is needed by humans because humans, on the other hand, feel weak with their limitations and some have certain advantages in humans. This is where the need for leaders and leadership arises, especially in an institution that always communicates with other humans in an organized manner that requires a leader to have more abilities and then appointed or appointed as the person entrusted with dealing with other people, both formal and non-formal organizations. Leaders in educational institutions at the senior secondary level are called school principals.The method used in this journal is the literature study method. A leader must have a motivator spirit that subordinates to psychological theory. A leader in carrying out his activities trying to solve problems must use sociological theory. A good leader who is good at creating a conducive work environment can use supportive theory, as well as being flexible in exercising his leadership based on personal behavior theory. Leaders must have high emotional intelligence in the trait theory and leaders who are good at dealing with any situation are in situation theory. Leadership is all behavior related to the duties of a leader.